EFFECT OF DIFFERENT WATER REGIMES ON BIOMETRIC TRAITS OF SOME TOLERANT AND sensitive Tomato Genotypes - F. Shamim; 2; K. Farooq; A. Waheed (Journal of Animal and Plant Sciences, 2014)
Eleven local/exotic tomato genotypes were examined thoroughly to estimate the reduction in crop growth and yield at different water regimes i.e., at 80% of field capacity (optimum watered) 60% and 40% of field capacity (water deficit) conditions. Among all the genotypes, genotype L. pennelli out yielded followed by CLN1767 and L. chilense in terms of dry biomass and fruits as compared to rest of the genotypes.Lower water stress regimes(60 and 40% field capacities) further reduced significantly leaf area index. Whereas, CLN1767 and Lyallpur-1 were intermediate in total number of fruits. Lowest number of fruits but amazingly greater single fruit weight was recorded in Roma and Ratan at even 40% moisture regime. In view of these results, it could thus be concluded that considerable genetic variation exists in tomato and water stress tolerance that is associated with better adaption to water stress and can be used in breeding for stress tolerance.
Keywords: Tomato; Dry matter; Water stress regimes; Fruit size; Total soluble solids